2010
DOI: 10.1016/j.cardfail.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Potential Mechanisms of Red Cell Distribution Width as a Prognostic Marker in Heart Failure

Abstract: Background: Adverse outcomes have recently been linked to elevated red cell distribution width (RDW) in heart failure. Our study sought to validate the prognostic value of RDW in heart failure and to explore the potential mechanisms underlying this association. Methods and Results: Data from the Study of Anemia in a Heart Failure Population (STAMINA-HFP) registry, a prospective, multicenter cohort of ambulatory patients with heart failure supported multivariable modeling to assess relationships between RDW a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
305
4
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(346 citation statements)
references
References 28 publications
(24 reference statements)
16
305
4
11
Order By: Relevance
“…was suggested as another mechanism of prognostic value of RDW [22,23]. Red blood cells have a powerful antioxidant capacity and function as a primary oxidative sink; they are prone to oxidative damage which decreases cell survival and they increase the release of juvenile erythrocytes into circulation.…”
Section: Discussionmentioning
confidence: 99%
“…was suggested as another mechanism of prognostic value of RDW [22,23]. Red blood cells have a powerful antioxidant capacity and function as a primary oxidative sink; they are prone to oxidative damage which decreases cell survival and they increase the release of juvenile erythrocytes into circulation.…”
Section: Discussionmentioning
confidence: 99%
“…the risk assessment and determination of prognosis in patients with coronary artery disease, hypertension, HF, acute coronary syndrome, stroke, and peripheral arterial disease, and in patients undergoing coronary artery bypass surgery [1][2][3][6][7][8][9][10][11].…”
Section: Conflict Of Interest: None Declaredmentioning
confidence: 99%
“…Until now RDW has been used mainly as an auxiliary marker in haematology indicating the increased destruction or impaired production of red blood cells. Several studies have reported that elevated RDW levels are associated with poor outcomes in patients with such cardiovascular diseases as coronary artery disease, idiopathic pulmonary hypertension, chronic heart failure (HF), and severe aortic stenosis after transcatheter aortic valve implantation [1][2][3][4][5]. Its prognostic utility in patients undergoing aortic valve replacement surgery is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous investigations have shown that RDW and PDW are significantly associated diseases including chronic spontaneous urticaria and gram-negative bacteremia (3)(4)(5). Furthermore, RDW has also been regarded as a prognostic marker for certain diseases, such as stable angina pectoris (6,7).…”
Section: Introductionmentioning
confidence: 99%